Preparation method of isotropic Ti2AlNb / TiAl-based interpenetrating composite material

By designing the TPMS configuration reinforcement frame and vacuum hot press sintering process, isotropic Ti2AlNb/TiAl-based interpenetrating composite material was prepared, which solved the problems of poor room temperature plasticity and toughness and strong mechanical properties of TiAl-based composite material. The multi-directional strength and toughness matching of composite materials is achieved, providing a new application solution for aerospace power systems.

CN119282142AActive Publication Date: 2025-01-10NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411476768.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

TiAl matrix composite materials have limited their application in aerospace field, including poor plasticity, poor toughness and strong mechanical properties.

Method used

Isotropic Ti2AlNb/TiAl-based interpenetrating composite material was designed and prepared. The TPMS configuration reinforcement body skeleton was designed through implicit function modeling. The SLM forming was used to form the selected laser melting process, and combined with the vacuum hot press sintering HPS process, the composite material was realized. Good match for strength, plasticity and toughness.

Benefits of technology

It effectively avoids the strong anisotropy of traditional fiber-reinforced composites, improves the multi-directional strength and toughness matching of TiAl matrix composites, and provides a new solution for the hot-end components of the aerospace power system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005096324580000011
    Figure HDA0005096324580000011
  • Figure HDA0005096324580000021
    Figure HDA0005096324580000021
  • Figure HDA0005096324580000022
    Figure HDA0005096324580000022
Patent Text Reader

Abstract

The invention provides a preparation method of an isotropic Ti2AlNb / TiAl-based interpenetrating composite material, and belongs to the technical field of intermetallic compound-based composite materials. The method comprises the following steps: firstly, designing a Ti2AlNb reinforcement framework of various TPMS configurations by utilizing implicit function modeling; then, carrying out anisotropy research on the TPMS configuration by utilizing finite element simulation; secondly, a Ti2AlNb reinforcement framework of a TPMS configuration is prepared through a selective laser melting (SLM) technology; and finally, the TPMS configuration Ti2AlNb / TiAl-based interpenetrating composite material is prepared through vacuum hot pressing sintering of HPS. Therefore, strong anisotropy of a traditional fiber reinforced composite material in mechanical property is avoided, good matching of strength, plasticity and toughness of the composite material is achieved, and a new thought and a new solution are provided for breaking through the application bottleneck of TiAl in spaceflight power system hot end components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of intermetallic compound-based composite materials, and particularly relates to a method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material. Background Art

[0002] In addition to inheriting the excellent properties of the TiAl matrix itself, TiAl-based composites also have the excellent elastic modulus and room temperature / high temperature strength of the reinforcement, thereby achieving a good match of strength, plasticity and toughness of the composite at room temperature / high temperature. At present, common TiAl-based composites include particle / whisker reinforced and continuous fiber reinforced TiAl-based composites. However, the mechanical properties of some TiAl-based composites have limited improvement effects, and there are problems such as strong anisotropy, which are still obstacles to their development. In order to meet the growing performance requirements of lightweight structural materials in the aerospace field, there is an urgent need to further develop and design a new TiAl-based composite material.

[0003] In recent years, researchers have tried to improve the strength and plasticity of TiAl-based composites by adjusting the configuration of reinforcements and have made some substantial progress. For example, Wang et al. successfully prepared Ti2AlN / TiAl-based composites with a network distribution of reinforcements by spark plasma sintering technology (YPWang, TFMa, Z, X.Chen, et.al. Superior high-temperature strength-ductility of TiB2-Ti2AlN / TiAl composite with core-shell microstructure[J]. Materials Science and Engineering: A, 2024, 889: 145873.). Li et al. prepared TiB2-Ti2AlN / TiAl composites with unidirectional, orthogonal and M-shaped fiber arrangements by adjusting the distribution of continuous fibers. f / TiAl based composite materials. The results show that when the fibers are arranged unidirectionally along the load direction, they exhibit the best combination of strength and plasticity, when they are arranged orthogonally, the performance is the worst, and when they are arranged in a cross-shaped pattern, the performance is between the two (Li Jinguang. TiNb f / TiAl composites: Microstructure evolution characteristics and mechanical properties regulation [D]. Xi'an: Northwestern Polytechnical University, 2023: 28-53.). It can be seen that the design of reinforcement configuration is a crucial step in improving the mechanical properties of composites.

[0004] "Natural selection" drives organisms to evolve structural materials with high specific strength, high toughness, and high impact toughness. This is essentially a competition between different structural forms, resulting in various toughening mechanisms. More interestingly, organisms have competitively selected triply periodic minimal surfaces (TPMS) during long-term evolution. For example, TPMS structures have been found in butterfly wing scales, weevil exoskeletons, and mantis shrimp maxillopods (B. Winter, B. Butza, C. Dieker, et.al. Coexistence of both gyroid chiralities in individual butterfly wing scales of Callophrys rubi[J]. Proceedings of the National Academy of Science of the United States of America, 2015, 112:12911-12916.). Following the natural example, Sun et al. used digital photopolymerization technology to print two zirconia ceramic reinforcement frameworks for TPMS structures. They then infiltrated the frameworks with epoxy resin to produce zirconia / epoxy resin-based interpenetrating composites. The results showed that both uniform and gradient TPMS structure-reinforced composites exhibited significantly higher strength and fracture toughness than the reinforcement frameworks (JX Sun, SX Yu, JW Zhu, et al. 3D printing of ceramic composite with biomimetic toughening design [J]. Additive Manufacturing, 2022, 58: 103027). Meanwhile, Gao et al. prepared a metal-based three-dimensional interpenetrating biomimetic composite using pressureless infiltration technology, which exhibited high specific strength and excellent energy absorption capacity (Gao Meng, Feng Heyang, Huo Juntao, et al. A metal-based three-dimensional interpenetrating biomimetic composite and its preparation method [P]. Publication No. CN 117961032A). Numerous studies have shown that TPMS structural reinforcement frameworks offer advantages in structural design, mechanical properties, and formability. For example, the structure features smooth transitions, avoiding stress concentration at truss-like lattice nodes. Furthermore, in terms of mechanical properties, the TPMS exhibits a more uniform stress-strain distribution under load and exhibits less anisotropy. In summary, research on TPMS-configured Ti2AlNb / TiAl-based interpenetrating composites is urgent in order to obtain TiAl-based composites with high strength and toughness at room temperature and isotropic mechanical properties. Summary of the Invention

[0005] The technical problem solved by the present invention is to provide a method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material. In view of the problems of TiAl alloys such as poor room temperature plasticity and toughness and strong anisotropy of mechanical properties, the present invention designs and prepares a high-strength and toughness Ti2AlNb / TiAl-based interpenetrating composite material, thereby avoiding the strong anisotropy of mechanical properties of traditional fiber-reinforced composite materials and achieving good matching of strength, plasticity and toughness of the composite material in multiple directions.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing isotropic Ti2AlNb / TiAl based interpenetrating composite materials, see Figure 1 As shown, the preparation method is specifically divided into two parts:

[0008] (1) Design and preparation of TPMS Ti2AlNb reinforcement skeleton; the specific process is as follows:

[0009] Step 1: Implicit function modeling of TPMS configurations: Use implicit function modeling to design Ti2AlNb reinforcement skeletons for various TPMS configurations. The specific operation method is as follows:

[0010] Typical TPMS lattice structures (e.g., Gyroid, Primitive, Diamond, and Split-P) were selected and implicit function modeling was performed using nTopology commercial software to obtain a CAD model of the lattice structure, such as Figure 2 As shown in the figure, the model used for SLM forming by selective laser melting process is exported as an stl model file;

[0011] Specific parameter information of the Ti2AlNb reinforcement skeleton of the TPMS configuration in the above CAD model: the unit cell size is 5×5×5mm 3 , the number of unit cells in the x, y and z directions are all 6.

[0012] Step 2: Finite element simulation of the Ti2AlNb reinforcement skeleton of the TPMS configuration: Use finite element simulation to study the anisotropy of the Ti2AlNb reinforcement skeleton of the TPMS configuration; specific operation method:

[0013] Based on the CAD model of the Ti2AlNb reinforcement skeleton of the TPMS configuration designed in step 1, the lattice structure is meshed with the help of nTopology software; using the homogenization method and finite element simulation, periodic boundary conditions are applied to the unit cells of the Ti2AlNb reinforcement skeleton of different TPMS configurations to obtain the elastic properties of the lattice structure, such as Figure 3 shown.

[0014] The mesh division shape is a tetrahedron with a size of 0.3 mm.

[0015] Step 3: Prepare the Ti2AlNb reinforcement skeleton of the TPMS configuration using the selective laser melting process (SLM). The specific process is as follows:

[0016] Step 3-1: Slicing and pre-printing processing of the Ti2AlNb reinforcement skeleton of the TPMS configuration formed by the selective laser melting process SLM

[0017] First, the CAD model of the lattice structure obtained above was imported into Materialise Magics software for slicing. The processed file was then imported into the FF-M140C machine. Next, a titanium alloy substrate was placed in the forming cavity, and Ti-22Al-25Nb powder was added to the powder cavity. The position of the substrate was adjusted to ensure a uniform and complete powder layer covering the substrate surface. Finally, high-purity argon gas was used to dilute and exhaust the oxygen in the forming cavity and pipelines until the oxygen content in the cavity was below 200 ppm.

[0018] The slice layer thickness of the above-mentioned lattice structure is 0.03 mm.

[0019] Step 3-2: Selective laser melting (SLM) of the Ti2AlNb reinforcement skeleton in the TPMS configuration;

[0020] By adjusting the laser input density, mainly including laser power, scanning speed, scanning spacing and powder layer thickness, the selective laser melting process SLM forming of the lattice structure is achieved; after the printing is completed, wait for the substrate temperature to drop to room temperature, use the electric spark wire cutting equipment to cut the lattice structure from the substrate, ultrasonically clean it and dry it for later use, completing the selective laser melting process SLM forming of the Ti2AlNb reinforcement skeleton, such as Figure 4 shown.

[0021] The laser power is 150-250W, the scanning speed is 800-1400mm / s, the scanning spacing is 0.1mm, and the powder layer thickness is 0.03mm; the laser scanning strategy is chessboard scanning, and the scanning direction between adjacent layers is rotated 67°; the substrate preheating temperature is controlled at 90°.

[0022] Step 3-3: Surface treatment of the Ti2AlNb reinforcement skeleton of the TPMS configuration;

[0023] The Ti2AlNb reinforcement skeleton of the TPMS structure formed by the selective laser melting (SLM) process was electropolished to remove the unmelted powder particles adhering to the skeleton surface during the forming process.

[0024] (2) Vacuum hot pressing sintering HPS composite forming of Ti2AlNb / TiAl based interpenetrating composite materials; the specific process is as follows:

[0025] Step 4: Prepare a Ti2AlNb / TiAl-based interpenetrating composite material with TPMS structure by vacuum hot pressing and sintering HPS. The specific operation process is as follows:

[0026] Step 4-1: Pre-pressing of TPMS-configured Ti2AlNb / TiAl-based interpenetrating composite materials;

[0027] First, a TPMS-structured Ti2AlNb reinforcement skeleton was placed in a graphite mold coated with yttria. Then, a certain mass of TiAl powder was poured into the skeleton. During the filling process, ultrasonic vibration was used to reduce the gaps between the powders, making the powders densely packed and increasing the tap density of the TiAl powder. Finally, the graphite mold containing the TPMS-structured Ti2AlNb reinforcement skeleton and TiAl powder was placed in a vacuum hot-pressing sintering furnace and pre-pressed at room temperature under a certain pressure.

[0028] Based on the CAD model designed in step 1, by controlling the bias parameter C of the TPMS structure, a reinforcement skeleton with a volume fraction of 7.5-37.5 vol.% can be obtained; the required TiAl powder mass can be calculated by the formula m = ρ × (0.625-0.925) × πr 2 ×h is calculated; where ρ is the density of TiAl alloy (g / cm 3 ); r is the radius of the graphite mold (mm); h is the height of the Ti2AlNb reinforcement of the TPMS structure (mm);

[0029] The pre-pressing pressure at room temperature is selected to be 5-10 MPa, and the holding time is 10-30 minutes.

[0030] Step 4-2: Vacuum hot pressing sintering HPS of TPMS-structured Ti2AlNb / TiAl-based interpenetrating composite materials

[0031] The pre-pressed green compact is placed in a vacuum hot pressing sintering furnace and HPS formed under specific sintering parameters. After the sample cools to room temperature in the furnace, the block is removed from the mold to obtain a Ti2AlNb / TiAl-based interpenetrating composite material with a diameter of 60 mm and a height of 10 mm.

[0032] The sintering parameters of vacuum hot pressing HPS are as follows: sintering temperature is 1050-1250℃, holding time is 0.5-2h, and pressure is 45MPa. During the vacuum hot pressing HPS sintering process, when the temperature reaches 600℃, it is kept at this temperature for 10 minutes to remove the residual included gas in the graphite mold. The heating rate is 5-10℃ / min, and the oxygen content must be kept below 200ppm throughout the process.

[0033] In the above step 3, the chemical composition of the Ti2AlNb powder used for selective laser melting (SLM) forming is as follows: Al: 22-25 at.%, Nb: 20-30 at.%, Ta: 0-7 at.%, and the remainder is Ti, and the powder particle size is 15-53 μm; in the above step 4, the chemical composition of the TiAl powder used for composite forming is as follows: Al: 45-48 at.%, Cr: 1-3 at.%, Nb: 2-5 at.%, and the remainder is Ti, and the powder particle size is 50-150 μm.

[0034] The advantages of the present invention compared with the prior art are:

[0035] 1. This proposal addresses the problems of room-temperature plasticity, poor toughness, and strong anisotropy in mechanical properties of TiAl alloys. A high-strength and toughness Ti2AlNb / TiAl-based interpenetrating composite material was designed and prepared. First, implicit function modeling was used to design Ti2AlNb reinforcement frameworks with various TPMS configurations. Then, finite element simulation was used to study the anisotropy of the TPMS configuration. Second, the Ti2AlNb reinforcement framework with TPMS configuration was prepared using selective laser melting (SLM). Finally, a TPMS-configured Ti2AlNb / TiAl-based interpenetrating composite material was prepared by vacuum hot press sintering (HPS). This approach avoids the strong anisotropy in mechanical properties of traditional fiber-reinforced composites, achieving a good match between the strength, plasticity, and toughness of the composite material. This provides a new approach and solution for breaking through the application bottleneck of TiAl in hot-end components of aerospace propulsion systems.

[0036] 2. This proposal utilizes SLM technology for the first time to produce an isotropic Ti2AlNb reinforcement framework in a TPMS configuration, which is then used to strengthen and toughen TiAl-based interpenetrating composites. Compared to the cross-laminated reinforcements used in existing technologies, this TPMS configuration offers high strength, low stress concentration, and low anisotropy, thus avoiding the strong anisotropy in mechanical properties of traditional fiber-reinforced and laminated composites. It achieves an excellent match of strength, plasticity, and toughness in multiple directions for TiAl-based composites.

[0037] 3. In the prior art of this proposal, the continuity of the three-dimensional continuous structure reinforcement skeleton is inevitably destroyed during the composite forming process under high temperature and high pressure conditions, reducing its strengthening and toughening effect. However, this proposal proposes the following measures to reduce the tendency of skeleton collapse and deformation during the HPS forming process, thereby reducing its impact on mechanical properties:

[0038] 1) The selected TiAl powder has a smooth surface, good sphericity, less satellite powder and hollow powder, and improves the bulk density of the powder;

[0039] 2) After TiAl powder is filled into the TPMS Ti2AlNb reinforcement skeleton, ultrasonic vibration is used to reduce the gaps between the powders, making the powders densely packed, thereby increasing the tap density of the TiAl powder;

[0040] 3) Before HPS forming, a graphite mold containing a TPMS-structured Ti2AlNb reinforcement skeleton and TiAl powder is pre-pressed under a pressure of 5-10 MPa to give the TiAl-based composite material a higher initial density;

[0041] Metallographic observation of the longitudinal cross-section of the HPS-formed composites using these measures revealed that the reinforcement framework had been lowered by 0.5 mm in the axial direction, with deformation limited to 5.6%-10%. In cross-sectional microstructure, the framework showed virtually no deformation. These results demonstrate that the Ti2AlNb reinforcement framework in the TPMS configuration produced by this process has a negligible effect on the anisotropy of the mechanical properties of the TiAl-based interpenetrating composites. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Flowchart of the present invention.

[0043] Figure 2 CAD model diagram of the Ti2AlNb reinforcement skeleton of the TPMS configuration in the present invention; a is the Gyroid structure, b is the Primitive structure, c is the Diamond structure, and d is the Split P structure;

[0044] Figure 3 Figure 1 is a diagram showing the elastic modulus distribution of the Ti2AlNb reinforcement skeleton in the TPMS configuration of the present invention in the xy, xz, and yz directions; in the figure, a is the xy direction, b is the xz direction, and c is the yz direction;

[0045] Figure 4 This is a macroscopic photograph of the Ti2AlNb reinforcement skeleton formed by SLM in the present invention;

[0046] Figure 5The room temperature compressive stress-strain curves of the Ti2AlNb reinforcement skeletons with different TPMS configurations formed by SLM in the present invention;

[0047] Figure 6 Figure 3 is a compressive stress-strain curve of the Ti2AlNb / TiAl-based interpenetrating composite material in different directions in the present invention; a, b, c and d in the figure correspond to Gyroid, Primitive, Diamond and Split P configuration Ti2AlNb / TiAl-based composite materials, respectively. DETAILED DESCRIPTION

[0048] The following is a combination of the embodiments of the present invention Figure 1-6 The technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments derived by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts are within the scope of protection of the present invention.

[0049] Example 1:

[0050] To address the issues of room-temperature plasticity and poor toughness of TiAl alloys, as well as their strong anisotropy of mechanical properties, this example designs and prepares a high-strength and toughness Ti2AlNb / TiAl-based interpenetrating composite material. First, implicit function modeling is used to design Ti2AlNb reinforcement frameworks in various TPMS configurations. Finite element simulation is then used to investigate the anisotropy of the TPMS configurations. Secondly, SLM technology is used to prepare Ti2AlNb reinforcement frameworks in TPMS configurations. Finally, the TPMS-configured Ti2AlNb / TiAl-based interpenetrating composite material is prepared using the HPS process. This approach avoids the strong anisotropy of mechanical properties associated with traditional fiber-reinforced composites, achieving a well-matched strength, plasticity, and toughness of the composite material. This provides a new approach and solution for overcoming the bottleneck in the application of TiAl in hot-end components of aerospace propulsion systems.

[0051] The chemical composition of the Ti2AlNb powder used for SLM in this embodiment is: Al (22-25 at.%), Nb (20-30 at.%), Ta (0-7 at.%), with the balance being Ti. The powder particle size is 15-53 μm. The chemical composition of the TiAl powder used for composite forming is: Al (45-48 at.%), Cr (1-3 at.%), and Nb (2-5 at.%), with the balance being Ti. The powder particle size is 50-150 μm.

[0052] The preparation process of the Ti2AlNb / TiAl-based interpenetrating composite material involved in this embodiment is specifically divided into two parts:

[0053] (1) Design and preparation of TPMS Ti2AlNb reinforcement skeleton. The specific process is as follows:

[0054] Step 1: Implicit function modeling of TPMS configuration.

[0055] Typical TPMS lattice structures (e.g., Gyroid, Primitive, Diamond, and Split-P) were selected and implicit function modeling was performed using nTopology commercial software to obtain a CAD model of the lattice structure, such as Figure 2 As shown. Among them, the model used for SLM forming is exported as an stl model file. In this embodiment, the lattice structure selected is Gyroid, and its surface can be described by the following expression:

[0056] φ G (x,y,z)=cos(X)·sin(Y)+cos(Y)·sin(Z)+cos(Z)·sin(X)-C (1)

[0057] Among them, X = 2πx / l, Y = 2πy / l, Z = 2πz / l, C is the bias parameter, and l is the unit length in the x, y, and z directions. Specific parameter information of the TPMS structure in the above CAD model: the unit cell size is 5×5×5mm 3 , the number of unit cells in the x, y and z directions is 6×6×6.

[0058] Step 2: Finite element simulation of the Ti2AlNb reinforcement skeleton in TPMS configuration

[0059] Based on the CAD model of the TPMS structure designed in step 1, the lattice structure is meshed with the help of nTopology software. Homogenization method and finite element simulation are used to apply periodic boundary conditions on the unit cells of different TPMS structures to obtain the elastic properties of the lattice structure, such as Figure 3 shown.

[0060] The mesh is divided into tetrahedrons with a size of 0.3 mm. The performance parameters of Ti2AlNb used for finite element simulation are as follows: elastic modulus, yield strength and tensile strength are 104.2 GPa, 943.0 MPa and 992.6 MPa respectively, Poisson's ratio is 0.3, and density is 5.3 g / cm 3 .

[0061] Step 3: Prepare the TPMS structure Ti2AlNb reinforcement skeleton using the selective laser melting process SLM;

[0062] Step 3-1: Slicing and pre-printing processing of SLM-molded skeleton

[0063] First, the CAD model of the Gyroid lattice structure obtained above was imported into Materialise Magics software for slicing. The diameter of the reinforcement skeleton was 60 mm, the height was 10 mm, and the slice layer thickness was 0.03 mm, for a total of 400 layers. The processed file was then imported into the FF-M140C equipment. Secondly, a titanium alloy substrate was placed in the forming cavity, and Ti-22Al-25Nb powder was loaded into the powder cavity. The position of the substrate was adjusted to ensure that the upper surface of the substrate was covered with a uniform and complete powder layer. Finally, high-purity argon gas was used to dilute and exhaust the oxygen in the forming cavity and pipeline until the oxygen content in the cavity was less than 200 ppm.

[0064] Step 3-2: SLM forming of TPMS structure Ti2AlNb reinforcement skeleton

[0065] By adjusting the laser input density, mainly including laser power, scanning speed, scanning spacing and powder layer thickness, the SLM forming of the lattice structure is achieved. After printing, wait for the substrate temperature to drop to room temperature, use the wire-cut EDM equipment to cut the lattice structure from the substrate, ultrasonically clean it and dry it for later use, completing the SLM forming of the Ti2AlNb reinforcement skeleton. Figure 4 shown.

[0066] The laser power was 250W, the scanning speed was 1200mm / s, the scanning pitch was 0.1mm, and the powder layer thickness was 0.03mm. The laser scanning strategy was a checkerboard scan, with the scanning direction rotated 67° between adjacent layers. The substrate preheat temperature was controlled at 90°.

[0067] Step 3-3: Surface treatment of TPMS Ti2AlNb reinforcement skeleton

[0068] The Ti2AlNb reinforcement skeleton of the TPMS structure formed by SLM was electropolished to remove the unmelted powder particles adhering to the surface of the skeleton during the forming process.

[0069] (2) HPS composite forming of Ti2AlNb / TiAl based interpenetrating composite materials. The specific process is:

[0070] Step 4: Prepare TPMS structure Ti2AlNb / TiAl based interpenetrating composite materials by vacuum hot pressing and sintering HPS;

[0071] Step 4-1: Pre-pressing of Ti2AlNb / TiAl-based interpenetrating composite materials

[0072] First, a TPMS-configured Ti2AlNb reinforcement skeleton was placed in a graphite mold coated with yttria. Then, a certain mass of TiAl powder was poured into the skeleton. During the filling process, ultrasonic vibration was used to reduce the gaps between the powders, making the powders tightly packed, thereby increasing the tap density of the TiAl powder. Finally, the graphite mold containing the reinforcement skeleton and TiAl powder was placed in a vacuum hot-pressing sintering furnace and pre-pressed at room temperature under a certain pressure.

[0073] Based on the CAD model designed in step 1, by controlling the bias parameter C of the TPMS structure, a reinforcement skeleton with a volume fraction of 30 vol.% can be obtained. The required TiAl powder mass can be calculated by the formula m = ρ × 0.7 × πr 2 ×h is calculated. Where ρ is the density of TiAl alloy (g / cm 3 ); r is the radius of the TPMS configuration (mm); h is the height of the Ti2AlNb reinforcement of the TPMS structure (mm).

[0074] The pre-pressing pressure at room temperature is selected to be 10 MPa, and the holding time is 20 minutes.

[0075] Step 4-2: HPS forming of Ti2AlNb / TiAl based interpenetrating composites

[0076] The pre-pressed green compact was placed in a vacuum hot-pressing sintering furnace and subjected to HPS forming under specific sintering parameters. After the sample cooled to room temperature in the furnace, the block was removed from the mold to obtain a Ti2AlNb / TiAl-based interpenetrating composite material with a diameter of 60 mm and a height of 10 mm.

[0077] The HPS sintering parameters are: sintering temperature of 1150°C, holding time of 1 hour, and pressure of 45 MPa. During the HPS process, after reaching 600°C, the temperature is held for 10 minutes to remove residual gas inclusions in the graphite mold. The heating rate is 5-10°C / min, and the oxygen content must be maintained below 200 ppm throughout the process.

[0078] The elastic modulus of the Gyroid skeleton prepared in this embodiment is completely coincident in the projections of the xy, xz and yz planes, showing excellent isotropy, and its yield strength reaches 206.3 MPa; and the compressive strength of the Gyroid-structured Ti2AlNb / TiAl-based interpenetrating composite material formed by HPS is the highest along the z-axis, reaching 1993.9 MPa, and the compressive strength along the x-axis is the lowest, at 1797.8 MPa, and the compressive strength along the y-axis is between the two, as shown in FIG. Figure 5 and 6 shown.

[0079] Example 2:

[0080] To address the issues of room-temperature plasticity and poor toughness of TiAl alloys, as well as their strong anisotropy of mechanical properties, this example designs and prepares a high-strength and toughness Ti2AlNb / TiAl-based interpenetrating composite material. First, implicit function modeling is used to design Ti2AlNb reinforcement frameworks in various TPMS configurations. Finite element simulation is then used to investigate the anisotropy of the TPMS configurations. Secondly, SLM technology is used to prepare Ti2AlNb reinforcement frameworks in TPMS configurations. Finally, the TPMS-configured Ti2AlNb / TiAl-based interpenetrating composite material is prepared using the HPS process. This approach avoids the strong anisotropy of mechanical properties associated with traditional fiber-reinforced composites, achieving a well-matched strength, plasticity, and toughness of the composite material. This provides a new approach and solution for overcoming the bottleneck in the application of TiAl in hot-end components of aerospace propulsion systems.

[0081] The chemical composition of the Ti2AlNb powder used for SLM in this embodiment is: Al (22-25 at.%), Nb (20-30 at.%), Ta (0-7 at.%), with the balance being Ti. The powder particle size is 15-53 μm. The chemical composition of the TiAl powder used for composite forming is: Al (45-48 at.%), Cr (1-3 at.%), and Nb (2-5 at.%), with the balance being Ti. The powder particle size is 50-150 μm.

[0082] The preparation process of the Ti2AlNb / TiAl-based interpenetrating composite material involved in this embodiment is specifically divided into two parts:

[0083] (1) Design and preparation of TPMS Ti2AlNb reinforcement skeleton. The specific process is as follows:

[0084] Step 1: Implicit function modeling of TPMS configuration

[0085] Typical TPMS lattice structures (e.g., Gyroid, Primitive, Diamond, and Split-P) were selected and implicit function modeling was performed using nTopology commercial software to obtain a CAD model of the lattice structure, such as Figure 2 As shown. Among them, the model used for SLM forming is exported as an stl model file. In this embodiment, the lattice structure selected is Primitive, and its surface can be described by the following expression:

[0086] φ P (x,y,z)=cos(X)+cos(Y)+cos(Z)-C (2)

[0087] Among them, X = 2πx / l, Y = 2πy / l, Z = 2πz / l, C is the bias parameter, and l is the unit length in the x, y, and z directions. Specific parameter information of the TPMS structure in the above CAD model: the unit cell size is 5×5×5mm 3 , the number of unit cells in the x, y and z directions is 6×6×6.

[0088] Step 2: Finite element simulation of the Ti2AlNb reinforcement skeleton in TPMS configuration

[0089] Based on the CAD model of the TPMS structure designed in step 1, the lattice structure is meshed with the help of nTopology software. Homogenization method and finite element simulation are used to apply periodic boundary conditions on the unit cells of different TPMS structures to obtain the elastic properties of the lattice structure, such as Figure 3 shown.

[0090] The mesh is divided into tetrahedrons with a size of 0.3 mm. The performance parameters of Ti2AlNb used for finite element simulation are as follows: elastic modulus, yield strength and tensile strength are 104.2 GPa, 943.0 MPa and 992.6 MPa respectively, Poisson's ratio is 0.3, and density is 5.3 g / cm 3 .

[0091] Step 3: Prepare the TPMS structure Ti2AlNb reinforcement skeleton using the selective laser melting process SLM;

[0092] Step 3-1: Slicing and pre-printing processing of SLM-molded skeleton

[0093] First, the CAD model of the Primitive lattice structure obtained above was imported into the MaterialiseMagics software for slicing. The diameter of the reinforcement skeleton was 60 mm, the height was 10 mm, and the slice layer thickness was 0.03 mm, for a total of 400 layers. Then, the processed file was imported into the FF-M140C equipment. Secondly, the titanium alloy substrate was placed in the forming cavity, and Ti-22Al-25Nb powder was filled into the powder cavity. By adjusting the position of the substrate, the upper surface of the substrate was covered with a uniform and complete powder layer. Finally, high-purity argon gas was used to dilute and exhaust the oxygen in the forming cavity and pipeline until the oxygen content in the cavity was less than 200 ppm.

[0094] Step 3-2: SLM forming of TPMS-structured Ti2AlNb reinforcement skeleton.

[0095] By adjusting the laser input density, mainly including laser power, scanning speed, scanning spacing and powder layer thickness, the SLM forming of the lattice structure is achieved. After printing, wait for the substrate temperature to drop to room temperature, use the wire-cut EDM equipment to cut the lattice structure from the substrate, ultrasonically clean it and dry it for later use, completing the SLM forming of the Ti2AlNb reinforcement skeleton. Figure 4 shown.

[0096] The laser power was 250W, the scanning speed was 1200mm / s, the scanning pitch was 0.1mm, and the powder layer thickness was 0.03mm. The laser scanning strategy was a checkerboard scan, with the scanning direction rotated 67° between adjacent layers. The substrate preheat temperature was controlled at 90°.

[0097] Step 3-3: Surface treatment of TPMS Ti2AlNb reinforcement skeleton

[0098] The Ti2AlNb reinforcement skeleton of the TPMS structure formed by SLM was electropolished to remove the unmelted powder particles adhering to the surface of the skeleton during the forming process.

[0099] (2) HPS composite forming of Ti2AlNb / TiAl based interpenetrating composite materials. The specific process is:

[0100] Step 4: Prepare the Ti2AlNb / TiAl-based interpenetrating composite material with TPMS structure by vacuum hot pressing and sintering HPS;

[0101] Step 4-1: Pre-pressing of Ti2AlNb / TiAl-based interpenetrating composite materials

[0102] First, a TPMS-configured Ti2AlNb reinforcement skeleton was placed in a graphite mold coated with yttria. Then, a certain mass of TiAl powder was poured into the skeleton. During the filling process, ultrasonic vibration was used to reduce the gaps between the powders, making the powders tightly packed, thereby increasing the tap density of the TiAl powder. Finally, the graphite mold containing the reinforcement skeleton and TiAl powder was placed in a vacuum hot-pressing sintering furnace and pre-pressed at room temperature under a certain pressure.

[0103] Based on the CAD model designed in step 1, by controlling the bias parameter C of the TPMS structure, a reinforcement skeleton with a volume fraction of 30 vol.% can be obtained. The required TiAl powder mass can be calculated by the formula m = ρ × 0.7 × πr 2 ×h is calculated. Where ρ is the density of TiAl alloy (g / cm 3 ); r is the radius of the TPMS configuration (mm); h is the height of the Ti2AlNb reinforcement of the TPMS structure (mm).

[0104] The pre-pressing pressure at room temperature is selected to be 10 MPa, and the holding time is 20 minutes.

[0105] Step 4-2: HPS forming of Ti2AlNb / TiAl based interpenetrating composite materials.

[0106] The pre-pressed green compact was placed in a vacuum hot-pressing sintering furnace and subjected to HPS forming under specific sintering parameters. After the sample cooled to room temperature in the furnace, the block was removed from the mold to obtain a Ti2AlNb / TiAl-based interpenetrating composite material with a diameter of 60 mm and a height of 10 mm.

[0107] The HPS sintering parameters are: sintering temperature of 1150°C, holding time of 1 hour, and pressure of 45 MPa. During the HPS process, after reaching 600°C, the temperature is held for 10 minutes to remove residual gas inclusions in the graphite mold. The heating rate is 5-10°C / min, and the oxygen content must be maintained below 200 ppm throughout the process.

[0108] The projections of the elastic modulus of the Primitive skeleton prepared in the embodiment in the xy, xz and yz planes completely coincide, and all show weak anisotropy. When the loading direction changes from

[001] to

[011] , the elastic modulus value gradually increases; the yield strength of the Primitive skeleton reaches 148.2 MPa; and the Primitive structure Ti2AlNb / TiAl-based interpenetrating composite material formed by HPS has the highest compressive strength along the x-axis, reaching 2075.2 MPa, and the lowest compressive strength along the y-axis, which is 1752.4 MPa, and the compressive strength along the z-axis is between the two, as shown in FIG. Figure 5 and 6 shown.

[0109] Example 3:

[0110] To address the issues of room-temperature plasticity and poor toughness of TiAl alloys, as well as their strong anisotropy of mechanical properties, this example designs and prepares a high-strength and toughness Ti2AlNb / TiAl-based interpenetrating composite material. First, implicit function modeling is used to design Ti2AlNb reinforcement frameworks in various TPMS configurations. Finite element simulation is then used to investigate the anisotropy of the TPMS configurations. Secondly, SLM technology is used to prepare Ti2AlNb reinforcement frameworks in TPMS configurations. Finally, the TPMS-configured Ti2AlNb / TiAl-based interpenetrating composite material is prepared using the HPS process. This approach avoids the strong anisotropy of mechanical properties associated with traditional fiber-reinforced composites, achieving a well-matched strength, plasticity, and toughness of the composite material. This provides a new approach and solution for overcoming the bottleneck in the application of TiAl in hot-end components of aerospace propulsion systems.

[0111] The chemical composition of the Ti2AlNb powder used for SLM in this embodiment is: Al (22-25 at.%), Nb (20-30 at.%), Ta (0-7 at.%), with the balance being Ti. The powder particle size is 15-53 μm. The chemical composition of the TiAl powder used for composite forming is: Al (45-48 at.%), Cr (1-3 at.%), and Nb (2-5 at.%), with the balance being Ti. The powder particle size is 50-150 μm.

[0112] The preparation process of the Ti2AlNb / TiAl-based interpenetrating composite material involved in this embodiment is specifically divided into two parts:

[0113] (1) Design and preparation of TPMS Ti2AlNb reinforcement skeleton. The specific process is as follows:

[0114] Step 1: Implicit function modeling of TPMS configuration

[0115] Typical TPMS lattice structures (e.g., Gyroid, Primitive, Diamond, and Split-P) were selected and implicit function modeling was performed using nTopology commercial software to obtain a CAD model of the lattice structure, such as Figure 2 As shown. Among them, the model used for SLM forming is exported as an stl model file. In this embodiment, the lattice structure selected is Diamond, and its surface can be described by the following expression:

[0116] φ D (x,y,z)=sin(X)·sin(Y)·sin(Z)+cos(X)·cos(Y)·cos(Z)-C (3)

[0117] Among them, X = 2πx / l, Y = 2πy / l, Z = 2πz / l, C is the bias parameter, and l is the unit length in the x, y, and z directions. Specific parameter information of the TPMS structure in the above CAD model: the unit cell size is 5×5×5mm 3 , the number of unit cells in the x, y and z directions is 6×6×6.

[0118] Step 2: Finite element simulation of the Ti2AlNb reinforcement skeleton in TPMS configuration

[0119] Based on the CAD model of the TPMS structure designed in step 1, the lattice structure is meshed with the help of nTopology software. Homogenization method and finite element simulation are used to apply periodic boundary conditions on the unit cells of different TPMS structures to obtain the elastic properties of the lattice structure, such as Figure 3 shown.

[0120] The mesh is divided into tetrahedrons with a size of 0.3 mm. The performance parameters of Ti2AlNb used for finite element simulation are as follows: elastic modulus, yield strength and tensile strength are 104.2 GPa, 943.0 MPa and 992.6 MPa respectively, Poisson's ratio is 0.3, and density is 5.3 g / cm 3 .

[0121] Step 3: Prepare the Ti2AlNb reinforcement skeleton of TPMS configuration using the selective laser melting process SLM;

[0122] Step 3-1: Slicing and pre-printing processing of the SLM-formed skeleton.

[0123] First, the CAD model of the Diamond lattice structure obtained above was imported into Materialise Magics software for slicing. The diameter of the reinforcement skeleton was 60 mm, the height was 10 mm, and the slice layer thickness was 0.03 mm, for a total of 400 layers. The processed file was then imported into the FF-M140C equipment. Secondly, the titanium alloy substrate was placed in the forming cavity, and Ti-22Al-25Nb powder was filled into the powder cavity. The position of the substrate was adjusted to ensure that the upper surface of the substrate was covered with a uniform and complete powder layer. Finally, high-purity argon gas was used to dilute and exhaust the oxygen in the forming cavity and pipeline until the oxygen content in the cavity was less than 200 ppm.

[0124] Step 3-2: SLM forming of TPMS-structured Ti2AlNb reinforcement skeleton.

[0125] By adjusting the laser input density, mainly including laser power, scanning speed, scanning spacing and powder layer thickness, the SLM forming of the lattice structure is achieved. After printing, wait for the substrate temperature to drop to room temperature, use the wire-cut EDM equipment to cut the lattice structure from the substrate, ultrasonically clean it and dry it for later use, completing the SLM forming of the Ti2AlNb reinforcement skeleton. Figure 4 shown.

[0126] The laser power was 250W, the scanning speed was 1200mm / s, the scanning pitch was 0.1mm, and the powder layer thickness was 0.03mm. The laser scanning strategy was a checkerboard scan, with the scanning direction rotated 67° between adjacent layers. The substrate preheat temperature was controlled at 90°.

[0127] Step 3-3: Surface treatment of TPMS Ti2AlNb reinforcement skeleton

[0128] The Ti2AlNb reinforcement skeleton of the TPMS structure formed by SLM was electropolished to remove the unmelted powder particles adhering to the surface of the skeleton during the forming process.

[0129] (2) HPS composite forming of Ti2AlNb / TiAl based interpenetrating composite materials. The specific process is:

[0130] Step 4: Prepare the Ti2AlNb / TiAl-based interpenetrating composite material with TPMS structure by vacuum hot pressing and sintering HPS;

[0131] Step 4-1: Pre-pressing of Ti2AlNb / TiAl-based interpenetrating composite materials

[0132] First, a TPMS-configured Ti2AlNb reinforcement skeleton was placed in a graphite mold coated with yttria. Then, a certain mass of TiAl powder was poured into the skeleton. During the filling process, ultrasonic vibration was used to reduce the gaps between the powders, making the powders tightly packed, thereby increasing the tap density of the TiAl powder. Finally, the graphite mold containing the reinforcement skeleton and TiAl powder was placed in a vacuum hot-pressing sintering furnace and pre-pressed at room temperature under a certain pressure.

[0133] Based on the CAD model designed in step 1, by controlling the bias parameter C of the TPMS structure, a reinforcement skeleton with a volume fraction of 30 vol.% can be obtained. The required TiAl powder mass can be calculated by the formula m = ρ × 0.7 × πr 2 ×h is calculated. Where ρ is the density of TiAl alloy (g / cm 3 ); r is the radius of the TPMS configuration (mm); h is the height of the Ti2AlNb reinforcement of the TPMS structure (mm).

[0134] The pre-pressing pressure at room temperature is selected to be 10 MPa, and the holding time is 20 minutes.

[0135] Step 4-2: HPS forming of Ti2AlNb / TiAl based interpenetrating composite materials.

[0136] The pre-pressed green compact was placed in a vacuum hot-pressing sintering furnace and subjected to HPS forming under specific sintering parameters. After the sample cooled to room temperature in the furnace, the block was removed from the mold to obtain a Ti2AlNb / TiAl-based interpenetrating composite material with a diameter of 60 mm and a height of 10 mm.

[0137] The HPS sintering parameters are: sintering temperature of 1150°C, holding time of 1 hour, and pressure of 45 MPa. During the HPS process, after reaching 600°C, the temperature is held for 10 minutes to remove residual gas inclusions in the graphite mold. The heating rate is 5-10°C / min, and the oxygen content must be maintained below 200 ppm throughout the process.

[0138] The elastic modulus of the Diamond skeleton prepared in the embodiment completely overlaps in the projections of the xy, xz and yz planes, showing excellent isotropy, and its yield strength reaches 209.7MPa; and the Diamond configuration Ti2AlNb / TiAl based interpenetrating composite material formed by HPS has the highest compressive strength along the x-axis direction, reaching 1921.6MPa, and the lowest compressive strength along the z-axis direction, which is 1820.8MPa, while the compressive strength along the y-axis is between the two. At this time, the TiAl based interpenetrating composite material shows isotropy, such as Figure 5 and 6 shown.

[0139] Example 4:

[0140] To address the issues of room-temperature plasticity and poor toughness of TiAl alloys, as well as their strong anisotropy of mechanical properties, this example designs and prepares a high-strength and toughness Ti2AlNb / TiAl-based interpenetrating composite material. First, implicit function modeling is used to design Ti2AlNb reinforcement frameworks in various TPMS configurations. Finite element simulation is then used to investigate the anisotropy of the TPMS configurations. Secondly, SLM technology is used to prepare Ti2AlNb reinforcement frameworks in TPMS configurations. Finally, the TPMS-configured Ti2AlNb / TiAl-based interpenetrating composite material is prepared using the HPS process. This approach avoids the strong anisotropy of mechanical properties associated with traditional fiber-reinforced composites, achieving a well-matched strength, plasticity, and toughness of the composite material. This provides a new approach and solution for overcoming the bottleneck in the application of TiAl in hot-end components of aerospace propulsion systems.

[0141] The chemical composition of the Ti2AlNb powder used for SLM in this embodiment is: Al (22-25 at.%), Nb (20-30 at.%), Ta (0-7 at.%), with the balance being Ti. The powder particle size is 15-53 μm. The chemical composition of the TiAl powder used for composite forming is: Al (45-48 at.%), Cr (1-3 at.%), and Nb (2-5 at.%), with the balance being Ti. The powder particle size is 50-150 μm.

[0142] The preparation process of the Ti2AlNb / TiAl-based interpenetrating composite material involved in this embodiment is specifically divided into two parts:

[0143] (1) Design and preparation of TPMS Ti2AlNb reinforcement skeleton. The specific process is as follows:

[0144] Step 1: Implicit function modeling of TPMS configuration

[0145] Typical TPMS lattice structures (e.g., Gyroid, Primitive, Diamond, and Split-P) were selected and implicit function modeling was performed using nTopology commercial software to obtain a CAD model of the lattice structure, such as Figure 2 As shown. Among them, the model used for SLM forming is exported as an stl model file. In this embodiment, the lattice structure selected is Split P, and its surface can be described by the following expression:

[0146] φ SP (x,y,z)=1.1[sin(2X)·cos(Y)·sin(Z)+sin(2Y)·cos(Z)·sin(X)+sin(2Z)cos(X)·sin(Y)]-0. 2[cos(2X)·cos(2Y)+cos(2Y)·cos(2Z)+cos(2Z)·cos(2X)]-0.4[cos(2Y)+cos(2Z)+cos(2X)]-C (4)

[0147] Among them, X = 2πx / l, Y = 2πy / l, Z = 2πz / l, C is the bias parameter, and l is the unit length in the x, y, and z directions. Specific parameter information of the TPMS structure in the above CAD model: the unit cell size is 5×5×5mm 3 , the number of unit cells in the x, y and z directions is 6×6×6.

[0148] Step 2: Finite element simulation of the Ti2AlNb reinforcement skeleton in TPMS configuration

[0149] Based on the CAD model of the TPMS structure designed in step 1, the lattice structure is meshed with the help of nTopology software. Homogenization method and finite element simulation are used to apply periodic boundary conditions on the unit cells of different TPMS structures to obtain the elastic properties of the lattice structure, such as Figure 3 shown.

[0150] The mesh is divided into tetrahedrons with a size of 0.3 mm. The performance parameters of Ti2AlNb used for finite element simulation are as follows: elastic modulus, yield strength and tensile strength are 104.2 GPa, 943.0 MPa and 992.6 MPa respectively, Poisson's ratio is 0.3, and density is 5.3 g / cm 3 .

[0151] Step 3: Prepare the Ti2AlNb reinforcement skeleton of TPMS configuration using the selective laser melting process SLM;

[0152] Step 3-1: Slicing and pre-printing processing of SLM-molded skeleton

[0153] First, the CAD model of the Split P lattice structure obtained above was imported into Materialise Magics software for slicing. The diameter of the reinforcement skeleton was 60 mm, the height was 10 mm, and the slice layer thickness was 0.03 mm, for a total of 400 layers. The processed file was then imported into the FF-M140C equipment. Secondly, a titanium alloy substrate was placed in the forming cavity, and Ti-22Al-25Nb powder was filled into the powder cavity. The position of the substrate was adjusted to ensure that the upper surface of the substrate was covered with a uniform and complete powder layer. Finally, high-purity argon gas was used to dilute and exhaust the oxygen in the forming cavity and pipeline until the oxygen content in the cavity was less than 200 ppm.

[0154] Step 3-2: SLM forming of TPMS-structured Ti2AlNb reinforcement skeleton.

[0155] By adjusting the laser input density, mainly including laser power, scanning speed, scanning spacing and powder layer thickness, the SLM forming of the lattice structure is achieved. After printing, wait for the substrate temperature to drop to room temperature, use the wire-cut EDM equipment to cut the lattice structure from the substrate, ultrasonically clean it and dry it for later use, completing the SLM forming of the Ti2AlNb reinforcement skeleton. Figure 4 shown.

[0156] The laser power was 250W, the scanning speed was 1200mm / s, the scanning pitch was 0.1mm, and the powder layer thickness was 0.03mm. The laser scanning strategy was a checkerboard scan, with the scanning direction rotated 67° between adjacent layers. The substrate preheat temperature was controlled at 90°.

[0157] Step 3-3: Surface treatment of TPMS Ti2AlNb reinforcement skeleton

[0158] The Ti2AlNb reinforcement skeleton of the TPMS structure formed by SLM was electropolished to remove the unmelted powder particles adhering to the surface of the skeleton during the forming process.

[0159] (2) HPS composite forming of Ti2AlNb / TiAl based interpenetrating composite materials. The specific process is:

[0160] Step 4: Prepare the Ti2AlNb / TiAl-based interpenetrating composite material with TPMS structure by vacuum hot pressing and sintering HPS;

[0161] Step 4-1: Pre-pressing of Ti2AlNb / TiAl-based interpenetrating composite materials

[0162] First, a TPMS-configured Ti2AlNb reinforcement skeleton was placed in a graphite mold coated with yttria. Then, a certain mass of TiAl powder was poured into the skeleton. During the filling process, ultrasonic vibration was used to reduce the gaps between the powders, making the powders tightly packed, thereby increasing the tap density of the TiAl powder. Finally, the graphite mold containing the reinforcement skeleton and TiAl powder was placed in a vacuum hot-pressing sintering furnace and pre-pressed at room temperature under a certain pressure.

[0163] Based on the CAD model designed in step 1, by controlling the bias parameter C of the TPMS structure, a reinforcement skeleton with a volume fraction of 30 vol.% can be obtained. The required TiAl powder mass can be calculated by the formula m = ρ × 0.7 × πr 2 ×h is calculated. Where ρ is the density of TiAl alloy (g / cm 3 ); r is the radius of the TPMS configuration (mm); h is the height of the Ti2AlNb reinforcement of the TPMS structure (mm).

[0164] The pre-pressing pressure at room temperature is selected to be 10 MPa, and the holding time is 20 minutes.

[0165] Step 4-2: HPS forming of Ti2AlNb / TiAl based interpenetrating composites

[0166] The pre-pressed green compact was placed in a vacuum hot-pressing sintering furnace and subjected to HPS forming under specific sintering parameters. After the sample cooled to room temperature in the furnace, the block was removed from the mold to obtain a Ti2AlNb / TiAl-based interpenetrating composite material with a diameter of 60 mm and a height of 10 mm.

[0167] The HPS sintering parameters are: sintering temperature of 1150°C, holding time of 1 hour, and pressure of 45 MPa. During the HPS process, after reaching 600°C, the temperature is held for 10 minutes to remove residual gas inclusions in the graphite mold. The heating rate is 5-10°C / min, and the oxygen content must be maintained below 200 ppm throughout the process.

[0168] The elastic modulus of the Split P skeleton prepared in this embodiment is completely coincident in the projections in the xy, xz and yz planes, showing excellent isotropy, and its yield strength reaches 240.9 MPa; and the compressive strength of the Split P structure Ti2AlNb / TiAl based interpenetrating composite material formed by HPS is the highest along the x-axis, reaching 2145.7 MPa, and the compressive strength along the z-axis is the lowest, at 2017.9 MPa, and the compressive strength along the y-axis is between the two, as shown in FIG. Figure 5 and 6 shown.

[0169] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.

[0170] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material, characterized in that: The preparation method is divided into two parts: (I) Design and preparation of TPMS configuration Ti2AlNb reinforcement skeleton; the specific process is: Step 1: Implicit function modeling of TPMS configuration: Various TPMS configuration Ti2AlNb reinforcement skeletons are designed using implicit function modeling; Step 2: Finite element simulation of the TPMS configuration Ti2AlNb reinforcement skeleton: The anisotropy of the TPMS configuration Ti2AlNb reinforcement skeleton is studied by finite element simulation; Step 3: Prepare the TPMS configuration Ti2AlNb reinforcement skeleton by selective laser melting (SLM); Step 3-1: Slicing and pre-printing processing of the Ti2AlNb reinforcement skeleton of the TPMS configuration formed by the selective laser melting process SLM; Step 3-2: Selective laser melting (SLM) of the TPMS-structured Ti2AlNb reinforcement skeleton; Step 3-3: Surface treatment of the TPMS configuration Ti2AlNb reinforcement skeleton; (ii) Vacuum hot pressing sintering HPS composite forming of Ti2AlNb / TiAl based interpenetrating composite materials; the specific process is as follows: Step 4: Prepare TPMS-structured Ti2AlNb / TiAl-based interpenetrating composite materials by vacuum hot pressing HPS Step 4-1: Pre-pressing of TPMS-structured Ti2AlNb / TiAl-based interpenetrating composite materials; Step 4-2: Vacuum hot pressing sintering HPS forming of TPMS structured Ti2AlNb / TiAl based interpenetrating composite materials.

2. The method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material according to claim 1, characterized in that: In step 1: various TPMS configuration Ti2AlNb reinforcement skeletons are designed using implicit function modeling. The specific operation method is as follows: A typical TPMS lattice structure was selected and implicit function modeling was performed using nTopology software to obtain a CAD model of the lattice structure; the model used for selective laser melting (SLM) was exported as an stl model file; In step 2: use finite element simulation to simulate the anisotropy of the Ti2AlNb reinforcement skeleton of the TPMS configuration. The specific operation method is: Based on the CAD model of the Ti2AlNb reinforcement skeleton of the TPMS configuration designed in step 1, the lattice structure is meshed with the help of nTopology software; the homogenization method and finite element simulation are used to apply periodic boundary conditions on the unit cells of the Ti2AlNb reinforcement skeleton of different TPMS configurations, so as to obtain the elastic properties of the lattice structure; The specific process of step 3: Step 3-1: Slicing and pre-printing processing of Ti2AlNb reinforced body skeleton of TPMS structure formed by selective laser melting process SLM First, the CAD model of the lattice structure obtained above was imported into the Materialise Magics software for slicing. Then, the processed file was imported into the FF-M140C equipment. Secondly, the titanium alloy substrate was placed in the forming cavity, and Ti-22Al-25Nb powder was filled into the powder cavity. The position of the substrate was adjusted so that a powder layer with uniform thickness and complete coverage was formed on the upper surface of the substrate. Finally, high-purity argon gas was used to dilute and exhaust the oxygen in the forming cavity and pipeline until the oxygen content in the cavity was less than 200ppm. Step 3-2: Selective laser melting (SLM) of the TPMS-structured Ti2AlNb reinforcement skeleton; By adjusting the laser input density, mainly including laser power, scanning speed, scanning spacing and powder layer thickness, the selective laser melting process SLM forming of the lattice structure is realized; after the printing is completed, when the substrate temperature drops to room temperature, the lattice structure is cut off from the substrate using an electric spark wire cutting device, and then dried after ultrasonic cleaning for standby use, thus completing the selective laser melting process SLM forming of the Ti2AlNb reinforcement skeleton; Step 3-3: Surface treatment of the Ti2AlNb reinforcement skeleton of the TPMS configuration; The Ti2AlNb reinforcement skeleton of the TPMS structure formed by the selective laser melting process (SLM) was electropolished to remove the unmelted powder particles adhering to the surface of the skeleton during the forming process. Specific operation process of step 4: Step 4-1: Pre-pressing of Ti2AlNb / TiAl-based interpenetrating composite materials in TPMS configuration; First, a TPMS-structured Ti2AlNb reinforcement skeleton is placed in a graphite mold coated with yttrium oxide. Then, a certain mass of TiAl powder is poured into the skeleton, and ultrasonic vibration is used to reduce the gap between the powders during the filling process, so that the powders are packed tightly and the tap density of the TiAl powder is increased. Finally, the graphite mold containing the TPMS-structured Ti2AlNb reinforcement skeleton and TiAl powder is placed in a vacuum hot-pressing sintering furnace and pre-pressed at room temperature under a certain pressure. Step 4-2: Vacuum hot pressing sintering HPS forming of TPMS structure Ti2AlNb / TiAl based interpenetrating composite materials The pre-pressed green sheet is placed in a vacuum hot pressing sintering furnace and HPS formed under specific sintering parameters; after the sample is cooled to room temperature in the furnace, the block is taken out from the mold to obtain a Ti2AlNb / TiAl-based interpenetrating composite material.

3. The method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material according to claim 2, characterized in that: In the above step 1, the specific parameter information of the TPMS configuration Ti2AlNb reinforcement skeleton in the CAD model: the unit cell size is 5×5×5mm 3 , the number of unit cells in the x, y and z directions are all 6.

4. The method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material according to claim 2, characterized in that: In the above step 2, the mesh division shape is a tetrahedron with a size of 0.3 mm.

5. The method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material according to claim 2, characterized in that: In the above step 3-1, the slice layer thickness of the lattice structure is 0.03 mm.

6. The method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material according to claim 2, characterized in that: In the above step 3-2, the laser power is 150-250W, the scanning speed is 800-1400mm / s, the scanning spacing is 0.1mm, and the powder layer thickness is 0.03mm; the laser scanning strategy is chessboard scanning, and the scanning direction between adjacent layers is rotated 67°; the substrate preheating temperature is controlled at 90°.

7. The method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material according to claim 2, characterized in that: In the above step 4-1, based on the CAD model designed in step 1, by controlling the mid-surface offset C of the TPMS structure, a reinforcement skeleton with a volume fraction of 7.5 to 37.5 vol.% can be obtained; the required TiAl powder mass can be obtained by the formula m = ρ × (0.625-0.925) × πr 2 ×h is calculated; where ρ is the density of TiAl alloy g / cm 3 ; r is the radius of the graphite mold in mm; h is the height of the Ti2AlNb reinforcement in the TPMS structure in mm; The pre-pressing pressure at room temperature is selected to be 5-10MPa, and the holding time is 10-30min.

8. The method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material according to claim 2, characterized in that: In the above step 4-2, the sintering parameters of vacuum hot pressing sintering HPS are: sintering temperature is 1050-1250°C, holding time is 0.5-2h, and pressure is 45MPa; during the vacuum hot pressing sintering HPS process, when the temperature reaches 600°C, it is kept warm for 10min to remove the residual included gas in the graphite mold, wherein the heating rate is 5-10°C / min, and the oxygen content must be kept below 200ppm throughout the process.

9. The method for preparing an isotropic Ti2AlNb / TiAl-based interpenetrating composite material according to claim 2, characterized in that: In the above step 3, the chemical composition of the Ti2AlNb powder used for selective laser melting SLM forming is: Al: 22-25 at.%, Nb: 20-30 at.%, Ta: 0-7 at.%, and the balance is Ti, and the powder particle size is 15-53 μm; In the above step 4, the chemical composition of the TiAl powder used for composite forming is: Al: 45-48at.%, Cr: 1-3at.%, Nb: 2-5at.%, and the remainder is Ti, and the powder particle size is 50-150μm.

Citation Information

Patent Citations

  • Method for preparing TiAl+Ti2AlNb composite materials by laser melting deposition

    CN110449581A

  • Tungsten enhancement copper composite and preparing method thereof

    CN111411254A

  • Preparation method of bionic interpenetrating Ti2AlNb / TiAl-based composite material

    CN116921697A

  • Metal-based three-dimensional interpenetrating bionic composite material and preparation method thereof

    CN117961032A

  • Design method of directional deformation mixed TPMS structure based on additive manufacturing

    CN118260944A

Cited By

  • Method and device for preparing lattice structure through multi-field auxiliary selective laser melting

    CN120055299A

  • Method and device for preparing a lattice structure by multi-field assisted selective laser melting

    CN120055299B

  • Broadband anti-sound double-lattice structure based on additive manufacturing as well as preparation method and application of broadband anti-sound double-lattice structure

    CN121104124A

  • Preparation method and application of high-entropy alloy TPMS network enhanced TiAl-based composite material

    CN121669965A

  • TiAl alloy and additive manufacturing composite process preparation method and application thereof

    CN121696411A